Human Immunodeficiency Virus Rev-Binding Protein Is Essential for Influenza A Virus Replication and Promotes Genome Trafficking in Late-Stage Infection - Eisfeld, Amie J. (American Society for Microbiology, 2011)
Influenza A virus uses cellular protein transport systems (e.g., CRM1-mediated nuclear export and Rab11-dependent recycling endosomes) for genome trafficking from the nucleus to the plasma membrane, where new virions are assembled. However, the detailed mechanisms of these events have not been completely resolved, and additional cellular factors are probably required. Here, we investigated the role of the cellular human immunodeficiency virus (HIV) Rev-binding protein (HRB), which interacts with influenza virus nuclear export protein (NEP), during the influenza virus life cycle. By using small interfering RNAs (siRNAs) and overexpression of a dominant negative HRB protein fragment, we show that cells lacking functional HRB have significantly reduced production of influenza virus progeny and that this defect results from impaired viral ribonucleoprotein (vRNP) delivery to the plasma membrane in late-stage infection. Since HRB colocalizes with influenza vRNPs early after their delivery to the cytoplasm, it may mediate a connection between the nucleocytoplasmic transport machinery and the endosomal system, thus facilitating the transfer of vRNPs from nuclear export to cytoplasmic trafficking complexes. We also found an association between NEP and HRB in the perinuclear region, suggesting that NEP may contribute to this process. Our results identify HRB as a second endosomal factor with a crucial role in influenza virus genome trafficking, suggest cooperation between unique endosomal compartments in the late steps of the influenza virus life cycle, and provide a common link between the cytoplasmic trafficking mechanisms of influenza virus and HIV.